Phosphorylated Fish Gelatin and the Quality of Jelly Gels: Gelling and Microbiomics Analysis - Shiyu Wu; Wanyi Sun; Yihui Yang; Ru Jia; Shengnan Zhan; Changrong Ou; Tao Huang (Foods, 2023)
Phosphorylated fish gelatin (PFG) exhibited preferable physical and chemical properties than fish gelatin (FG) in our previous study. To investigate the application values of PFG, the effects of different ratios (2:1, 1:1 and 1:2) of FG(PFG)/κ carrageenan (κC) on the quality of jelly gels (JGs) were investigated. The sensory quality of PFG:κC (1:2)/FG:κC (1:2) was found to be superior based on sensory evaluations, which was also verified with the results for texture, rheology, etc. Moreover, the structural changes in JGs were related to the introduction of phosphoric acid groups into the molecular chain of gelatin and the protein–polysaccharide interactions. According to the storage results, PFG jelly had better storage quality, higher hardness and chewiness values than those of FG jelly. High-throughput sequencing of JG microbial analysis showed that the addition of PFG changed the amount of microorganisms, microbial species abundance and the microbial composition of JGs, which were also closely related to the storage quality of JGs. In conclusion, the applications of PFG have promising potential to improve the quality of confectionery.